The differential impact of a 6-versus 12-month pharmacist-led interprofessional medication adherence program on medication adherence in patients with diabetic kidney disease: the randomized PANDIA-IRIS study - Bandiera, Carole; Dotta-Celio, Jennifer; Locatelli, Isabella; Nobre, Dina; Wuerzner, Grégoire; Pruijm, Menno; Lamine, Faiza; Burnier, Michel; Zanchi, Anne; Schneider, Marie Paule (Frontiers in Pharmacology, 2024)
Background Forty percents of patients with diabetes will develop diabetic kidney disease (DKD) over time. We aimed to evaluate the differential impact of a 6-versus 12-month pharmacist-led interprofessional medication adherence program (IMAP) on components of adherence (i.e., implementation and discontinuation) in patients with DKD, during and after the intervention. Methods All included patients benefited from the IMAP, which consists in face-to-face regular motivational interviews between the patient and the pharmacist based on the adherence feedback from electronic monitors (EMs). Patients were randomized 1:1 into two parallel arms: a 12-month IMAP intervention in group A, versus a 6-month intervention in group B. Adherence was monitored continuously for 24 months post-inclusion during the consecutive intervention and follow-up phases. Blood pressure was measured by the pharmacist at each visit. The repeated measures of daily patient medication intake outcomes (1/0) to medications were modelled longitudinally by generalized estimated equation in both groups, and in both the intervention and the follow-up phases. Results EM data of 72 patients were analyzed (34 in group A, 38 in group B). Patient implementation to antidiabetics and antihypertensive drugs increased during the IMAP intervention phase and decreased progressively during the follow-up period. At 12 months, implementation to antidiabetics was statistically higher in group A versus B, respectively of 93.8% versus 86.8% (Δ7.0%, 95%CI: 5.7%; 8.3%); implementation to antihypertensive drugs was also higher in group A versus B, respectively of 97.9% versus 92.1% (Δ5.8%, 95%CI: 4.8%; 6.7%). At 24 months, implementation to antidiabetics and antihypertensive drugs remained higher in group A versus B, respectively 88.6% versus 85.6% (Δ3.0%, 95%CI: 1.7%; 4.4%) for antidiabetics, and 94.4% versus 85.9% (Δ8.5%, 95%CI: 6.6%; 10.7%) for antihypertensive drugs. No difference in pharmacy-based blood pressure was observed between groups. Implementation to statins was comparable between groups. Three patients (all in group B) discontinued at least one treatment. Conclusions The IMAP improves adherence to chronic medications in patients with DKD. The longer the patients benefit from the intervention, the more the implementation increases over time, and the more the effect lasts after the end of the intervention. The impact on clinical outcomes needs to be demonstrated.